STUDY ON COTTON STEM FOR CELLULOSIC INDUSTRIES - Kamyar Salehi (Regional Information Center for Science and Technology (RICeST), 2003)
In order to investigate the possibility of utilizing cotton stem in cellulosic industries chemical, physical and anatomical properties of cotton stem (var. varamin) was investigated.Cotton wood fiber length, fiber diameter, lumen diameter and cell wall thickness was measured at 840 mm, 23.9mlm, 16/11mm, and 3/9mm respectively.Cotton stem oven-dry density, basic density, and air-dry density were measured at 0/44 gr./cm3, 0.4Ogr/cm3, and .42gr/cm3.Shrinkage and swelling was measured at 7.7 %, 8.3% and porosity was measured at 70.5%.Chemical composition was as follow: cellulose 52%, lignin 29.2%, ash 104% and extractives 6.8%.Anatomical features were as follow: Growth ring boundaries distinct or absent Wood diffuse-porous. Vessels in diagonal or radial pattern grouping:partly solitary partly in radial multiples of 2-4-6 or very small cluster Simple perforation plate. Intervesse pit alternate. Intervessel pit size: minute -< 4mm. Vestured pits absent. Vessel-ray pits with much reduced borders to apparently simple Helical Thickening absent. Mean tangential diameter of vessel lumina 50-100mm. Vessels per square millimeter 20-40 vessels. Mean vessel element length - < 350mm. Tyloses Gums & deposits absent. Fiber with simple to minutely bordered pits. Helical thickening in ground tissue fibers absent.Nonseptate fiber present. Fibers very thin walled. Rays with multi seriate portion as wide as uniseriate portion. Aggregate rays absent. Ray height> 1mm. Body ray cells procumbent with over 4 rows of upright  And square marginal cells Ray per millimeter 4-12/mm.